Reducing Environmental Impact on SME Metals Production Process Using Life Cycle Assessment and Analytical Hierarchy Process Method - Muhammad Faishal; Muhammad Noor Arfan; Hayati Mukti Asih (Jurnal Ilmiah Teknik Industri, 2020)
The ABC metal SME produces some wastes, such as liquid waste, solid waste, and smoke. The problem is hazardous waste dumped directly into the environment without any waste treatments which had bad impact on the environment around its SME. Therefore, this research is proposed to improve the production process of metal that can reduce the environmental impacts. The Life Cycle Assessment (LCA) method is developed to identify all the processes that have an impact on the environment and also to calculate the energy used. The values of environmental impact are calculated using Simapro 9.0 Software. In addition, Analytical Hierarchy Process (AHP) method is employed to determine the best alternative fuel according to four criteria, such as temperature, price, emission, and fuel consumption. The results show the process that has the greatest environmental impact is the metal smelting process. It is caused by the source fuel in this process was used oil. The usage of used oil can be the sources of air pollution that causing health problems in the respiratory tract such as bronchitis and asthma. Some alternative fuel was proposed, however, fuel gas is the best alternative among others according to the expert opinions. For the managerial insight, this research can be suggestion for SME to choose the best fuel in the production process that considering economic and environmental aspects.